Comparison of Maxillary Anterior Tooth Proportion Measurements Using Chu's Gauge and Digital Calipers in College Students - Vandersun Lestari; Cindy Denhara Wijaya; Aulia Hasanah Utari; Vania Pepayosa Sitepu (Jurnal Penelitian Pendidikan IPA, 2026)
Smile aesthetics is closely related to the proportion of the maxillary anterior teeth, which plays an important role in aesthetic dentistry. Standard evaluation tools such as Chu’s Esthetic Proportion Gauge, based on the Recurring Esthetic Dental (RED) proportion, are widely used to assess anterior tooth proportions. However, these standards were primarily developed from Caucasian populations and may not accurately represent dental characteristics in other populations. Considering the limited data on tooth proportion standards for the Indonesian population and the increasing demand for aesthetic dental treatment, evaluating the suitability of these tools in Indonesian individuals is important. This study aimed to assess the suitability of Chu’s Esthetic Proportion Gauge in measuring maxillary anterior tooth proportions and to compare its measurements with those obtained using a digital caliper among PSPDG FKKGIK Universitas Prima Indonesia students from the 2022–2024 cohorts. This quantitative comparative study employed a cross-sectional design involving 68 respondents selected through purposive sampling. Measurements of the central incisors, lateral incisors, and canines were conducted using Chu’s Gauge and a digital caliper. Data were analyzed using reliability testing, the Kolmogorov–Smirnov normality test, and the Mann–Whitney test. The results showed that both instruments demonstrated good reliability. However, significant differences were found between the measurements obtained using Chu’s Gauge and the digital caliper for all maxillary anterior teeth (p < 0.05), with the digital caliper consistently producing higher values. The highest agreement with Chu’s Gauge was observed in the central incisors, lower agreement in the lateral incisors, and no agreement in the canines. Gender-related differences in tooth proportions were also identified. These findings provide practical implications for aesthetic dental practice and contribute to the development of tooth proportion references for the Indonesian population. Future research should involve larger samples and explore advanced digital measurement methods to improve accuracy in assessing anterior tooth proportions.